1983
DOI: 10.1161/01.atv.3.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for peripheral atherosclerosis. Retrospective evaluation by stepwise discriminant analysis.

Abstract: To evaluate the optimal discriminators for peripheral atherosclerosis, we studied retrospectively 49 male patients and 39 male controls between 40 and 60 years of age. In addition to hypertension, cigarette smoking, diabetes mellitus, and hyperuricemia, we determined the most common tipids, lipoproteins, and apolipoproteins. Highly significant differences of median values between patients and controls in decreasing order of magnitude were recorded for apo A-ll/apo B, apo A-l/apo B, apo B, total cholesterol, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…53 The role of apoproteins D and E, 54 and the Lp(a) lipoprotein in relation to apo B and apo A-l and A-ll and their interaction in the genesis of atherosclerosis is as yet unknown.…”
Section: Future Questionsmentioning
confidence: 99%
“…53 The role of apoproteins D and E, 54 and the Lp(a) lipoprotein in relation to apo B and apo A-l and A-ll and their interaction in the genesis of atherosclerosis is as yet unknown.…”
Section: Future Questionsmentioning
confidence: 99%
“…It is not clear whether hyperuricemia is one of the independent risk factors and the reduction of serum uric acid concentrations improves the prognosis of patients with metabolic syndromes. The serum uric acid level is, however, at a good indicator of severity and prognosis of such patients with metabolic syndromes (9)(10)(11)(12)(13). Patients with hyperuricemia caused by metabolic syndrome have a large number of metabolic abnormalities and need several kinds of medicines if they attempt to treat each problem independently.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] These studies have, in general, shown that apoA-I levels are lower and that apoB levels are most often higher in patients with PAD. Also, 1 retrospective case-control study showed that cases with PAD had increased apoB/apoA-I ratio compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Also, 1 retrospective case-control study showed that cases with PAD had increased apoB/apoA-I ratio compared to controls. 26 Furthermore, it has been shown that apoB, rather than cholesterol, is an independent risk factor for development of PAD in smokers. 22 Results from the Apolipoprotein-related Mortality Risk (AMORIS) study 7 with 170 000 Swedish individuals showed that apoB was a better marker of cardiovascular risk than LDL, especially in individuals with desirable levels of LDL, regardless of sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation